IMPLEMENTASI PROGRAM SELARAS DALAM MEMOTIVASI MINAT BACA SISWA DI KELAS III SDN 11 SUMERTA DENPASAR - Ni Luh Made Ayu Mirandha Paramitha; I Made Wiguna Yasa; I Nyoman Artana (STKIP Subang, 2026)
Reading interest is an important factor in supporting literacy development and academic success among elementary school students. However, the reading interest of third-grade students at SDN 11 Sumerta Denpasar was still not optimal. To address this issue, the school implemented the Selaras Program (Tuesday Literacy Program) as a regular literacy activity. This study aimed to describe the implementation of the Selaras Program, identify the challenges and efforts involved in its implementation, and examine its impact on students’ reading motivation. This study employed a qualitative approach with a descriptive research design. Data were collected through observations, interviews, and documentation, and were analyzed through data reduction, data presentation, and conclusion drawing.The findings revealed that the Selaras Program was implemented through three stages: planning, implementation, and evaluation. The challenges encountered included differences in students’ reading abilities, lack of concentration, and low self-confidence. To address these challenges, teachers provided guidance, motivation, engaging learning media, and a variety of literacy activities. The Selaras Program had a positive impact on improving students’ learning motivation, reading interest, participation, and learning readiness.